Providensia Allah dalam Perspektif Nasihat Gamaliel: Kajian Teologis-Eksegetis - Galuh Pandandari (Sekolah Tinggi Teologi Sumatera Utara, 2025)
Gamaliel's advice in Acts 5:35–39 is an interesting statement into the dynamics of church growth and the early Christian movement. In the context of tension between Jewish religious authorities and the apostles, this advice not only reflects socio-political wisdom, but also contains significant theological hermeneutical principles. This study aims to explore in depth the theological meaning of Gamaliel's advice, its historical relevance, and its implications for the contemporary church in determining its stance toward contemporary spiritual movements. This study uses a literature review method with a historical-exegetical approach and public theology analysis. The novelty of this research lies in its emphasis on the principle of providential hermeneutics in understanding God's actions in church history and ministry, using Gamaliel's advice as an ethical and theological framework. The results of the research show that Gamaliel's advice reflects an implicit recognition of the possibility of God's involvement in events beyond the control of religious institutions. This principle teaches caution, humility, and trust in God's presence in every dynamic of ministry. In conclusion, understanding Gamaliel's principle encourages the church to respond to developments in ministry not with a reactive or coercive attitude, but with openness to the work of the Holy Spirit that transcend institutional structures. AbstrakNasihat Gamaliel dalam Kisah Para Rasul 5:35–39 menjadi pernyataan yang menarik dalam dinamika pertumbuhan gereja dan gerakan Kristen mula-mula. Dalam konteks ketegangan antara otoritas agama Yahudi dan para rasul, nasihat ini tidak hanya mencerminkan kebijaksanaan sosial-politis, tetapi mengandung prinsip hermeneutik teologis yang signifikan. Penelitian ini bertujuan untuk menelusuri secara mendalam makna teologis dari nasihat Gamaliel, relevansi historisnya, serta implikasinya bagi gereja masa kini untuk dapat menentukan sikap terhadap gerakan rohani kontemporer. Penelitian ini menggunakan metode studi literatur dengan pendekatan historis-eksegetis dan analisis teologi publik. Kebaruan dari penelitian ini terletak pada penekanan terhadap prinsip hermeneutika providensial dalam memahami tindakan Allah dalam sejarah gereja dan pelayanan, dengan menjadikan nasihat Gamaliel sebagai kerangka etis dan teologis. Hasil penelitian menunjukkan bahwa nasihat Gamaliel mencerminkan pengakuan implisit terhadap kemungkinan keterlibatan Allah dalam peristiwa-peristiwa di luar kendali lembaga keagamaan. Prinsip ini mengajarkan kehati-hatian, kerendahan hati, dan kepercayaan pada penyertaan Allah dalam setiap dinamika pelayanan. Kesimpulannya, pemahaman terhadap prinsip Gamaliel mendorong gereja untuk menanggapi perkembangan pelayanan bukan dengan sikap reaktif atau koersif, tetapi dengan keterbukaan pada pekerjaan Roh Kudus yang melampaui struktur-struktur institusional.